FAKTOR-FAKTOR YANG MENYEBABKAN KEJADIAN DANDRUFF PADA SISWI BERJILBAB DI SMA MUHAMMADIYAH 1 PEKANBARU - Azwika Yuni; Nurul Utami (Ensiklopedia of Journal, 2020)
Dandruff is excessive exfoliation of dead skin on the scalp with 50 % of post-publish global population. The use of the hijab is also closely related to the onset of dandruff. This study aims to determine the factors that cause dandruff incidence in female headscarf by by using Cross Sectional design. This type of research is quantitative. Sampling using Simple Random Sampling technique with 65 respondent sample in SMA Muhammadiyah 1 Pekanbaru on 9-11 August 2017. simple random sampling technique by drawing a member of the population (lottery technique) or drawing technique. The analysis used is univariate and bivariate, the measuring instrument used is questionnaire and data processing using computerized by using chi-square test. The results showed that there was a long relationship of wearing veil (p value 0,014), hair hygiene (p value 0,019), no relation of hijab material with dandruff incidence (p value 0,0335), stress was related to dandruff (p value 0,007) and diet is related to dandruff (p value 0,038). For respondents suggested that it can be used as input material for students in the health of the scalp especially about dandruff.